Transparency, access to information and credibility in the information - La Rosa Pinedo, Amaro (2009)
An appreciation os offered about the information transparency that focuses on the right to information of the states while proposing a model for a System of  Free Access to the States Information. Then, a brief analysis of the connection between credibility and transparency of politician is made